Using landsat satellite images and GIS to estimate and monitor the amount of absorbed CO2 in dipterocarp forest, Dak Lak province - Trinh, Huynh Thi Kieu; Duc, Bui Hien (Vietnam Journal of Science and Technology, 2018)
Dipterocarp forest is a typical ecosystem in Central Highlands of Vietnam and Dak Lak province. Dipterocarp forest plays significant role about biodiversity values, CO2 absorption and concentration. However, there is a lack of awareness of biological potentials in the local people after years of logging. It is necessary to collect data about forest biomass and carbon stored on maps by space and time in order to estimate and monitor CO2 absorbed in the large area. Hence, using GIS to develop relationships between biomass factor and carbon stock with digital values for monitoring carbon sequestration is important and meaningful in dipterocarp forest ecosystem; this method can generate the necessary database and information in terms of CO2 emission. The research results can create a basis for the dissemination and promotion of payment for environmental services according to REDD+ program. Unsupervised classification into 3-4-5 class and overlap forming combinations were close relationships with TAGTB derived from square plots (30x30m) and achieved confidence level 86.8% which were applied to estimate biomass and forest carbon through Landsat image. In this study, remote sensing and management of data in ArcGIS software through allometric equations model showed dipterocarp forest in Ea Soup and Ea Hleo districts (Dak Lak province) with a total area of 125,404.8 hectares and biomass tanks (above and below ground) of forest trees reaching at 8,156,667.6 tons. Total carbon was stored 4,093,501.1 tons. Total CO2 was absorbed 15,023,149.1 tons.